Սիրիա և Իսրայել․ չօգտագործված հնարավորությունները և ապագա հեռանկարները խաղաղության հաստատման համար (1991-2001) - Կարապետյան, Ռուբեն («Զանգակ - 97»)
For decades Egypt due ւօ it՝s Strategie and geografie centrality and resources has played a central role in the Arab-Israeli conflict. But, in 1979 after signing the Camp-David accurd witli Israel, that role has endcd and Israel՝s other influental ncighbour Syria took control over the Arab dimension of that conflict. Sinee that timethe Arab-Israeli conflicL bccame in many respects Syrian-Israeli conflict. This article analyzes the Syria՝ s role in the Arab-Israeli conflict as well as the regional and globa! background to the Syrian-Israeli dialoguc since the 1991 Madrid Conl'crcnce. It dcscribcs the long way that Syria and Israel had already gonc towards а pcacc agreement. The dcath of Hafiz al-Assad has brought a number of scrious questions. What does the fulurc hold in storc for Syria? Can Bashar consolidaic power? How will be the fulure of pcacc with Israel?
Keywords: Պատմություն; Քաղաքականություն